Relationship between motivation, locus of control, studying habits and performance in University Students from the Industrial and Systems Faculty from the National Engineering University - Fisfalen Huerta, Mario Heinrich (2016)
The academic performance of students depends on a number of factors, mostly psycological; within which studying habits play an important role, as well as student motivation and locus of control. In this work, a study of the relationship between academic performance, study habits, motivation and locus of control is made; analyzing the impact of the last three variables over the first. For which the survey technique is applied and scales of motivation, study habits and locus of control; analyzing the results with the use of statistical techniques such as correlation analysis, analysis of variance and correlation analysis. The study results show that the study habits and motivation for affiliation and motivation to achieve significant impact on the academic performance of the sample, formed by students of the School of Industrial and Systems Engineering.